Affirming Hifdz al-Daulah as Maqashid al-Syariah al-Daruriyyah in a Multicultural Nation-State: Its Implications for Social Harmony in Indonesia - Asa’ari, Asa’ari; Pitriani, Pitriani (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
The rise of radicalism and religious conservatism in Indonesia shows that multicultural nation-states are prone to social tensions when diversity values are not managed properly. Although various studies on maqashid al-shariah have discussed the dimension of al-Daruriyyat, there has been no study that systematically places hifz al-daulah as a component of daruriyyat in the context of a multicultural society and its implications for social harmony in Indonesia. This article aims to examine and analyse the urgency of hifdz al-daulah as part of maqashid shari'ah al-dharuriyah, as well as how hifdz al-daulah contributes to social harmonisation, thereby having implications for humanity and civilisation in Indonesia. This study uses a qualitative library research approach with textual analysis of classical literature (al-Syathibi, al-Mawardi) and contemporary maqashid literature (Auda), as well as a study of modern multiculturalism. Thematic-argumentative textual analysis was used in data analysis techniques, including data reduction, data presentation, and conclusions. The results of the study show that the placement of hifz al-daulah as part of daruriyyat has an adequate theoretical basis when linked to the function of the state in maintaining social stability and preventing (mafsadah) in a pluralistic society. This finding confirms that protecting the state as an institution that manages diversity is a prerequisite for achieving social harmony. In practical terms, this study contributes to the formulation of maqashid-based public policy and the development of a multicultural Islamic discourse in Indonesia.